A Commentary About the AMPHORA Study: Selected Caveats, Comments, and Considerations About Its Conditions of Diversity, Uncertainty, and Unpredictability. (15th October 2014) - Einstein, S.
Abstract : This point-of-view commentary explores a selected range of issues relevant to alcoholic beverage drinking and nondrinking patterns documented by the AMPHORA European study which, with hind-sight, limits its generalizability, with fore-sight are generally inadequately considered and documented and, with ordinary insight, are not likely to affect the ongoing and future behaviors of policy making and sustaining stakeholders whatever their sources of influence and whatever the levels and quality of evidence-informed data, information, and derived knowledge.